Hidronefrosis congénita. - Fernández Borrell, A.; Fernández Lucas, Cristina; Fuente Trabado, J.M. de la; Río Andreu, M. Del; Ballester Ortiz, G. (Clínicas Urológicas de la Complutense, 2002)
Sin resumen